A male gametophyte-specific monosaccharide transporter in Arabidopsis. - Truernit, Elisabeth; Stadler, Ruth; Baier, Kerstin; Sauer, Norbert (Plant Journal, 1999)
The AtSTP2 gene (sugar transport protein 2) of Arabidopsis thaliana encodes a high affinity, low specificity monosaccharide carrier that can transport a number of hexoses and pentoses at similar rates. AtSTP2 has 12 putative transmembrane helices and a molecular mass of 55.0 kDa. AtSTP2 expression was localized in AtSTP2 promoter-beta-glucuronidase (GUS) Arabidopsis plants showing AtSTP2-driven GUS activity during pollen maturation and also in germinating pollen. Immunohistochemical studies with anti-AtSTP2 antiserum as well as RNA in situ hybridization analyses modified these results and showed that AtSTP2 expression is confined to the early stages of gametophyte development. Both AtSTP2 mRNA and AtSTP2 protein are first seen at the time of beginning callose degradation and microspore release from the tetrades. AtSTP2 mRNA and AtSTP2 protein are no longer detected after the mitotic divisions and the formation of the trinucleate gametophyte. No AtSTP2 mRNA or AtSTP2 protein is seen in fully developed or germinating pollen. The putative role of AtSTP2 in the uptake of glucose units resulting from callose degradation during pollen maturation is discussed.